Systematic Literature Review: Using Podcasts as Media to Develop Listening Comprehension among EFL University Students - Ningrum, Suci Setia Cahya; Panggabean, Nuranisa (English Teaching and Linguistics Journal (ETLiJ), 2025)
Many EFL university students continue to face challenges in developing their listening skills, primarily due to limited access to engaging and authentic listening materials. Given that listening comprehension forms the foundation for overall language proficiency - particularly crucial at the tertiary level - finding effective solutions is essential. Podcasts emerge as a promising medium to address this need. This study investigates how podcasts can enhance listening skills among university-level EFL learners through a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. PRISMA's rigorous methodology ensures transparent, comprehensive, and reproducible research by following structured phases: identification, screening, and eligibility assessment. This approach enhances the study's validity by minimizing selection bias and providing clear criteria for article inclusion. From an initial pool of potential studies, 12 relevant articles published between 2016 and 2025 were systematically selected and analyzed. The findings reveal three key benefits of podcast implementation: (1) provision of authentic and varied listening materials, (2) flexible accessibility for anytime, anywhere learning, and (3) effective integration with metacognitive strategies. These results demonstrate podcasts' significant potential as a flexible, real-world-aligned pedagogical tool that can transform EFL listening instruction at the university level.